2022
DOI: 10.1101/2022.07.29.22277160
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

“I was scared dating… who would take me with my status?”- Living with HIV in the UTT era in Johannesburg, South Africa

Abstract: BACKGROUND South Africa rolled out Universal Test-and-Treat (UTT) in 2016, extending treatment eligibility to all persons living with HIV (PLHIV). Through this study, we sought to understand the experience of people living with HIV in the UTT era in South Africa. METHODS In May 2021, we conducted in-depth interviews (IDI) (N = 27) with adult (18 years and older) PLHIV referred by HIV counsellors at three peri-urban primary healthcare clinics. We also conducted three focus group discussions (FGDs) (N = 27) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 32 publications
(34 reference statements)
0
3
0
Order By: Relevance
“…Similar to previous studies, we found that PLHIV understand the health benefits of ART, with significant gaps in knowledge and only moderate confidence in U = U [ 10 , 18 , 19 ]. The scepticism was rooted in PLHIV’s limited VL literacy and challenges in understanding the implications of U = U for their relationships [ 20 , 21 ]. While the U = U approach to VL communication can facilitate HCPs’ partnerships with patients to improve their self-management, the potential benefits of U = U on ART adherence and the mental and emotional well-being of PLHIV are likely mediated by U = U belief among current and prospective partners [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar to previous studies, we found that PLHIV understand the health benefits of ART, with significant gaps in knowledge and only moderate confidence in U = U [ 10 , 18 , 19 ]. The scepticism was rooted in PLHIV’s limited VL literacy and challenges in understanding the implications of U = U for their relationships [ 20 , 21 ]. While the U = U approach to VL communication can facilitate HCPs’ partnerships with patients to improve their self-management, the potential benefits of U = U on ART adherence and the mental and emotional well-being of PLHIV are likely mediated by U = U belief among current and prospective partners [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…The scepticism was rooted in PLHIV’s limited VL literacy and challenges in understanding the implications of U = U for their relationships [ 20 , 21 ]. While the U = U approach to VL communication can facilitate HCPs’ partnerships with patients to improve their self-management, the potential benefits of U = U on ART adherence and the mental and emotional well-being of PLHIV are likely mediated by U = U belief among current and prospective partners [ 21 , 22 ]. However, HIV-negative/naïve persons in South Africa are largely unaware or sceptical of U = U [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation